The association of parental and offspring educational attainment with systolic blood pressure, fasting blood glucose and waist circumference in Latino adults - Jessica Cruz Whitley; Carmen A. Peralta; Mary Haan; Allison E. Aiello; Anne Lee; Julia Ward; Adina Zeki Al Hazzouri; John Neuhaus; Sally Moyce; Lenny López (Wiley, 2018)
Summary Objective The objective of the study is to evaluate the association of intergenerational educational attainment with cardiovascular disease (CVD) risk factors among US Latinos. Methods We used cross‐sectional data from the Niños Lifestyle and Diabetes Study, an offspring cohort of middle‐aged Mexican‐Americans whose parents participated in the Sacramento Latino Study on Aging. We collected educational attainment, demographic and health behaviours and measured systolic blood pressure (SBP), fasting glucose and waist circumference. We evaluated the association of parental, offspring and a combined parent-offspring education variable with each CVD risk factor using multivariable regression. Results Higher parental education was associated only with smaller offspring waist circumference. In contrast, higher offspring education was associated with lower SBP, fasting glucose and smaller waist circumference. Adjustment for parental health behaviours modestly attenuated these offspring associations, whereas adjustment for offspring health behaviours and income attenuated the associations of offspring education with offspring SBP and fasting glucose but not smaller waist circumference, even among offspring with low parental education. Conclusions Higher offspring education is associated with lower levels of CVD risk factors in adulthood, despite intergenerational exposure to low parental education.